2004
DOI: 10.1038/sj.bjp.0705644
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity analysis of a novel NR2C/NR2D‐preferring NMDA receptor antagonist: 1‐(phenanthrene‐2‐carbonyl) piperazine‐2,3‐dicarboxylic acid

Abstract: piperazine-2,3-dicarboxylic acid (PBPD) is a moderate affinity, competitive N-methyl-D-aspartate (NMDA) receptor antagonist with an atypical pattern of selectivity among NMDA receptor 2 subunit (NR2) subunits. We now describe the activity of several derivatives of PBPD tested at both rat brain NMDA receptors using L-[ 3 H]-glutamate binding assays and at recombinant receptors expressed in Xenopus oocytes. 2 Substituting various branched ring structures for the biphenyl group of PBPD reduced NMDA receptor activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
136
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(148 citation statements)
references
References 30 publications
(47 reference statements)
11
136
1
Order By: Relevance
“…PPDA was reported as a selective NR2D competitive antagonist at low concentrations, as we used, with an IC50 value of around 0.1 mM. 23,24,29 Although, PPDA was also reported as an antagonist of NR2C, in agreement with the absence of NR2C mRNA in our cultured cortical neurons, N2RC was only detected in the cerebellum, thalamus and olfactory bulb. 30 At low concentration, PPDA completely prevented the worsening effect of tPA on NMDA-induced neuronal death.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…PPDA was reported as a selective NR2D competitive antagonist at low concentrations, as we used, with an IC50 value of around 0.1 mM. 23,24,29 Although, PPDA was also reported as an antagonist of NR2C, in agreement with the absence of NR2C mRNA in our cultured cortical neurons, N2RC was only detected in the cerebellum, thalamus and olfactory bulb. 30 At low concentration, PPDA completely prevented the worsening effect of tPA on NMDA-induced neuronal death.…”
Section: Discussionsupporting
confidence: 80%
“…To address this question, we took advantage of the absence of NR2C subunits in our cell culture system ( Figure 3) and used phenanthrene derivative (2S*, 3R*)-1-(phenanthrene-2-carbonyl)piperazine-2,3-dicarboxylic acid (PPDA) at a concentration of 0.2 mM, earlier reported to inhibit NR2D-containing NMDAR. 23,24 In the presence of PPDA, the deleterious effect of tPA on NMDA-induced neuronal death was completely prevented (Figure 4a), supporting the actual involvement of NR2D-containing NMDAR. To further validate the hypothesis that NR2D subunit has an important function in NMDAR-mediated neurotoxicity, primary cultures of cortical neurons (12-14 DIV) were transiently transfected with Stealth RNA interference targeting NR2D.…”
Section: Resultsmentioning
confidence: 53%
“…7B). Finally, consistently with our Western blot analysis, when we tested the putative NR2A antagonist NVP-AAM077 (0.004 -4 M) (Auberson et al, 2002), we observed a similar dose-dependent inhibition of NMDAR-mediated responses both in control slices and in slices pretreated with cocaine (data not shown), although we need to point out that NVP-AAM077 might also bind NR2C-containing receptors (Feng et al, 2004). Together, our biochemical results suggest that acute cocaine causes increased expression of NR2B-containing NMDARs, specifically at the synaptic membrane, whereas our pharmacological results seem to suggest increased presence of functional NR1/NR2A/NR2B complexes, which are less sensitive to ifenprodil and Ro25-6981 antagonism, rather than dimeric NR1/NR2B NMDARs.…”
Section: Pharmacological and Biophysical Properties Of Cocainepotentisupporting
confidence: 79%
“…Given the sixfold greater sensitivity of NR2CD over NR2AB subunits to PPDA [21], these data suggest that NR2CD subunits are activated and contribute to the voltage and calcium waveforms of dendritic NMDA spikes.…”
Section: (D) Drugsmentioning
confidence: 84%